PENGARUH PEMBERIAN EDUKASI INSOMNIA TERHADAP PENINGKATAN PENGETAHUAN PADA MAHASISWA TPB SEKOLAH FARMASI ITB TAHUN AJARAN 2020/2021 - Agustania, Sindy
The term insomnia comes from the Latin words in and somnus. In means not or without, and somnus means sleep. Insomnia can affect productivity and can lead to other health problems that need to be addressed. However, lack of knowledge about insomnia can affect its treatment and prevention, so health education is necessary. The purpose of this study was to identify the effect of education to the level of knowledge and the level of sleep quality on TPB students of School of Pharmacy in Bandung Institute if Technology. This research is a cross-sectional descriptive study that was conducted concurrently using questionnaires and pre test-post test questions. The questionnaire used was the Pittsburgh Sleep Quality Index (PSQI) questionnaire to obtain data on the level of sleep quality and the SERVQUAL questionnaire to obtain data on respondents' satisfaction with education. The level of knowledge was measured using pre test-post test questions. The statistical analysis used is Friedman, Wilcoxon Test, and Chi square. The results of the study showed a significant relationship (p<0.05) before and after education was carried out on: the knowledge level of 107 respondents (97.27%) had increased ; and the sleep quality level of 64 respondents (58.18%) improved. There is no significant relationship (p=0.136) between the level of knowledge and the level of sleep quality of respondents after education and the correlation is weak (contingency coefficient = 0.187). The level of respondents' satisfaction with education shows an average result of 94.74 ± 1.1% and CV of 1.16% which indicates that respondents are very satisfied with the education provided.